2017
DOI: 10.18549/pharmpract.2017.01.827
|View full text |Cite
|
Sign up to set email alerts
|

Public knowledge, attitudes and practices regarding antibiotic use in Kosovo

Abstract: Background:Antimicrobial resistance is becoming a major public health challenge worldwide, caused primarily by the misuse of antibiotics. Antibiotic use is closely related to the knowledge, attitudes and behaviour of a population.Objective:The objective of this study was to assess the level of knowledge, attitudes and practices about antibiotic use among the general public in Kosovo.Methods:A cross-sectional face-to-face survey was carried out with a sample of 811 randomly selected Kosovo residents. The method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
58
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(67 citation statements)
references
References 29 publications
8
58
1
Order By: Relevance
“…Only a small proportion (1.5%) of the respondents received antibiotics without physician consultation. This self-medication rate was comparatively much lower than those reported in other studies conducted among adults, which were 5.3% to 20.4% in Malaysia [35,[39][40][41]44], and 22.4% to 76.6% in other countries [42,43,[45][46][47][48][49], in which respondents obtained antibiotics from the pharmacy without prescriptions, followed by antibiotics shared by family or friends, and purchased from clinics without consultation. A systematic review reported that age is not a strong determinant in self-medication with antibiotics [50]; therefore, the lower rate of self-medication in this study might not be due to subject selection for elderly population.…”
Section: Discussioncontrasting
confidence: 61%
“…Only a small proportion (1.5%) of the respondents received antibiotics without physician consultation. This self-medication rate was comparatively much lower than those reported in other studies conducted among adults, which were 5.3% to 20.4% in Malaysia [35,[39][40][41]44], and 22.4% to 76.6% in other countries [42,43,[45][46][47][48][49], in which respondents obtained antibiotics from the pharmacy without prescriptions, followed by antibiotics shared by family or friends, and purchased from clinics without consultation. A systematic review reported that age is not a strong determinant in self-medication with antibiotics [50]; therefore, the lower rate of self-medication in this study might not be due to subject selection for elderly population.…”
Section: Discussioncontrasting
confidence: 61%
“…In this study, 75% of people had taken an antibiotic treatment in the last 12 months preceding the survey. This prevalence was comparable to that found in Kuwait (72.8%) [24], while it was higher than those found in Ethiopia (46.7%) [25] and Kosovo (58.7%) [26].…”
Section: Prevalence Of Antibiotic Therapysupporting
confidence: 71%
“…Then 5% reused antibiotics leftover from their previous prescription. This proportion was 70.4% in Kosovo [26]. Lastly, 2% sourced antibiotics from the illicit market.…”
Section: Sources Of Supplymentioning
confidence: 97%
“…The majority of the studies (20 studies) were conducted as single-country studies while 2 studies were multi-country studies at global and regional levels [1,4]. Among the 20 singlecountry studies, 8 studies were conducted at national level [6,12,13,14,15,16,17,18] while the remaining 12 studies were conducted at sub-national level [11,19,20,21,22,23,24,25,26,27,28,29]. It should be noted that no study was conducted in the African region.…”
Section: Characteristic Of 22 Studiesmentioning
confidence: 99%